Clinical Signs of Poisoning with Pyrethroid and Cholinesterase Inhibitors - Farzad Gheshlaghi; Zohreh Sedighinia (مجله دانشکده پزشکی اصفهان, 2011)
Background: Due to the similarities between clinical signs of toxicity with pyrethroids and cholinesterase inhibitors, if the mistake between these two was made and the patient was treatment with atropine, severe atropine poisoning and even death could occur. This study was conducted to compare the clinical signs of two types of poisoning. Methods: In this cross-sectionsl study, 167 patients with pyrethroids poisoning and 167 patients with cholinesterase inhibitors poisoning refered to Noor hospital, Isfahan were assessed. The patients were selected by simple sampelling method and were clinically examined. Finding: The mean age of patients with pyrethroids poisoning was 22.47 and of patients with cholinesterase inhibitors poisoning was 28.80 years. In both groups, men were more than women and poisening by eating was the most prevalent way. The intentional cases were more than accidental ones. The most prevalent signs of cholinesterase inhibitors poisoning were nausea (68.9%), vomiting (43.1%), diarrhea (43.1%), myosis (40.7%), sweating (38.3%) and sialorrhea (36.5%) respectively; also, the most prevalent signs of pyrethroids poisoning were nausea (74.9%), vomiting (61.7%), abdominal cramp (20%), sialorrhea (15.6%), and muscle weakness (12.6%) respectively.